Clinical trial designs for rare diseases 2: trial protocols - Pariser, Anne (Henry Stewart Talks, 2019)
Master protocols in clinical trials, Examples of protocols in clinical trials, Basket trials, Umbrella trials, Platform trials, Selected examples of protocols in clinical trials